James Beard's theory & practice of good cooking - Beard, James, 1903-1985 (Running Press, 1999)
Based on Beard's 30 years of teaching experience, this volume is an authoritative kitchen reference featuring in-depth information on basic cooking techniques-from boiling, roasting, sautéing, and grilling to chilling and freezing. With recipes grouped according to their method of preparation, this practical cookbook is the definitive resource for all levels of culinary expertise-Publisher's description.